PSYCHOLOGICAL SAFETY FACTORS IN THE PROCESS OF TRAINING HIGHLY QUALIFIED PERSONNEL (Universal International Scientific Journal, 2026)
This article analyzes the theoretical foundations of the concept of psychological safety in the process of training highly qualified personnel. The study highlights the importance of creating an environment of psychological safety in the educational process, its role in the personal development of students, independent thinking, and the formation of professional competencies.
Keywords: psychological safety, highly qualified personnel, educational process, professional competence, personal development, socio-psychological climate, motivation, emotional intelligence, psychological stability.